THE EFFECT OF LEARNING CYCLE 7E MODEL ON IMPROVING THE MATHEMATICAL PROBLEM SOLVING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Mega Sukma Putri; Novi Trina Sari (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2021)
The purpose of this research was to find out the increase in the ability to understand mathematical problem solving of students after applied Learning Cycle 7E model and also was to find out the differences in problem solving abilities of students after applied Learning Cycle 7E model with conventional learning on SPLDV material in SMPN 6 Sabang. Kind of the research was used Quasi Experimental Design with pretest-posttest control group design. Population of this research are all of eight grade students in SMPN 6 Sabang. This research involves two class,VIII-1 as an experimental class and VIII-2 as a control class. Data was collected using test of students mathematical problem solving abilities.(1) Using the t-test (paired sample t-test) obtained tcount = 4,80 and ttable = 1,71. So because tcount ttable, it means refused and accept . So it can be concluded that the learning with used Learning Cycle 7E could increase mathematical problem solving abilities of students on SMPN 6 Sabang. As for the average increase is 0,30 in the medium category.(2) Based on the sample independent t-test, test of the criteria is refused if tcount ttable, because obtained tcount = 8,76 and ttable = 1,68. Because 8,76so accept . Based on the hypothesis test so it can be concluded that mathematical problem solving abilities of students SMPN 6 Sabang which applied with Learning Cycle 7E model there is a differences with mathematical problem solving abilities of students SMPN 6 Sabang which applied conventional learning.Keywords: Problem solving abilities, Learning Cycle 7E model